2017
DOI: 10.24198/pjd.vol29no3.14476
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol-containing mouthwash and alcohol-free mouthwash towards the power chains force decay

Abstract: Introduction: Power chains is the common device used in fixed orthodontic treatment. Force decay in power chains is a problem that can affect the teeth movement due to a continuous force cannot be maintained. Force decay in power chain can be affected by the use of alcohol-containing mouthwash or alcohol-free mouthwash. The objective of this study was to determine the effect of alcoholic-containing mouthwash, alcohol-free mouthwash, and artificial saliva towards the power chains force decay. Methods: This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…The results obtained from this study are in agreement with the results obtained in other studies regarding the effect of chlorhexidine (15)(16)(17)(18), ethyl alcohol (19)(20)(21) or cetylpyridine chloride (22)(23)(24) on the control of bacterial contamination of the brackets in patients undergoing orthodontic treatments with fixed appliances.…”
Section: Resultssupporting
confidence: 91%
“…The results obtained from this study are in agreement with the results obtained in other studies regarding the effect of chlorhexidine (15)(16)(17)(18), ethyl alcohol (19)(20)(21) or cetylpyridine chloride (22)(23)(24) on the control of bacterial contamination of the brackets in patients undergoing orthodontic treatments with fixed appliances.…”
Section: Resultssupporting
confidence: 91%
“…In this study, it was found that the majority of respondents had grade 3 traumatic stomatitis (lesion size 1-2 cm) (40%). These results are in line with a study conducted by Baricevic, where it was found that the most common lesions in patients with fixed orthodontics with metal used were erosions (7%), ulcerations (7%), contusions (7%), and desquamation ( 5%) due to trauma due to orthodontic appliances with a lesion size of 1-2 cm or grade 3 (Santana et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Traumatic stomatitis is inflammation of the oral mucosa caused by the use of orthodontic appliances, it can be due to discomfort when using orthodontic appliances, allergies to orthodontic appliance materials, pinched or punctured oral mucosa (Diah et al, 2019) or due to mechanical trauma due to tooth contact that injures the mouth. oral mucosa, sharp-structured food (Santana et al, 2017). In this study, it was found that the majority of respondents had grade 3 traumatic stomatitis (lesion size 1-2 cm) (40%).…”
Section: Discussionmentioning
confidence: 61%
“…Saliva itself also causes force decay, although to a lesser extent than mechanic tension and it only becomes significant weeks after the start of their application [ 8 ]. Means of personal oral hygiene such as mouthwashes, toothpastes, and the scouring effect from toothbrushes also affects the value of force [ 30 ]. Due to the ever-increasing latex allergy among patients, use of latex-free elastic chains became widespread during procedures.…”
Section: Discussionmentioning
confidence: 99%